Crude Oil Volatility Transmission Across Food Commodity Markets: A Multivariate BEKK-GARCH Approach. (August 2020) - Thenmozhi, M.; Maurya, Shipra
This study examines the time-varying price risk transmission in the nexus between crude oil and agricultural commodity prices in the context of non-grain-based biofuel producing country. Analysis of the short- and long-run dynamics of volatility in both spot and futures markets of maize, soybean and wheat and crude oil prices using the multivariate BEKK-GARCH model, indicate volatility spillover from wheat futures to crude oil futures in the short run and from crude oil futures to futures markets of maize, soybean and wheat in the long run. The spot market linkage of selected commodities is weaker compared to futures market, wherein maize spot volatility transmits to crude oil spot market in the longer period and no spillover between crude oil-food spot market is observed in the short run. The hedge ratios indicate that a dynamic hedging strategy is crucial for efficient risk management and the portfolio weights in futures market are more than the spot market. The results reveal that cross-market volatility spillover is more evident in the futures market, while own past conditional volatility is more significant in spot price discovery and risk transmission is evident among food commodities futures markets. JEL Codes: G13, G14, Q11, Q18, Q02